A virtual reality environment simulating drug use in schools: effect on emotions and mood states - Stavroulia, Kalliopi Evangelia; Baka, Evangelia; Christofi, Maria; Michael-Grigoriou, Despina; Magnenat-Thalmann, Nadia; Lanitis, Andreas (My University, 2018)
Virtual Reality (VR) can be exploited as a teacher-training tool promoting understanding of students’ problematic situations. This paper aims to investigate the potential of using VR for teacher training related to substance use by students. During the experiment participants were exposed to a virtual environment showing drug addicted students. Changes in participants’ emotional states before and after the exposure to the virtual environment were recorded using EEG measurements, heart rate recordings and self-reported data. The results indicate significant changes to participants’ negative emotional and mood states, suggesting that the VR experience had a strong impact on them.
Keywords: Virtual reality; Emotions; Substance use; Teacher education; Empathy